Analyzing Figurative Language in Taylor Swift’s Selected Songs: A Qualitative Study - Amalia MN, Ade Rezky (ASHLITION : Ash-Shahabah English Literature, Linguistics, & Education, 2024)
This study explores the use of figurative language in selected songs by Taylor Swift to understand its prevalence and impact. The primary objectives are to identify the types of figurative language used and determine the most dominant form. Employing a qualitative approach, this research analyzes five songs: "Bad Blood," "Blank Space," "Look What You Made Me Do," "End Game," and "You Belong With Me." The study utilizes the theoretical framework of Kennedy and Gioia to categorize figurative language into metaphors, similes, hyperboles, repetitions, symbols, and personifications. Findings reveal that metaphors are the most dominant, accounting for 38% of the figurative language, followed by hyperboles (24%) and repetitions (16%). The results underscore the role of figurative language in enriching song lyrics, creating depth, and enhancing listener engagement. These insights provide a foundation for further exploration of figurative language in contemporary music and its relevance to literary studies.